Effect of sodium rich pretreatments and processing conditions on microstructure and property evolution of sodium cobalt oxide thermoelectric materials - Jakubczyk, Ewa (Cranfield University, 2014)
Global environmental and sustainability issues have led to a growth in interest in oxide based thermoelectric materials. Sodium cobalt oxide, which presents low toxicity, is one of the most promising p-type thermoelectric materials for high temperature power generation applications. However, reproducibility and ease of manufacture limits its common use. NaCo2O4 bulk ceramic materials were prepared from powders synthesized using a solid state reaction (SSR) and sol gel (SG) method. The effect of time and temperature of treatment were investigated in order to determine their influence on microstructure and physical properties. The effects of three different Na-enriching pretreatments were evaluated with respect to microstructural evolution and their impact on thermoelectric and electric behaviour of the materials. Such modifications were found to be a critical factor affecting the microstructure of the bulk ceramic materials. The Na-rich pretreatments were found to improve density by up to 15%, increase electrical conductivity and help to compensate for Na loss at high sintering temperatures. The thermoelectric figure of merit ZT was found to increase for Na-rich pretreatment samples due to increases in Seebeck coefficient and low thermal conductivity. The highest value of ZT was found to be for the infiltration pretreatment where the value of 0.025 was observed at 350K. Na rich pretreatments, when compared with unpretreatment samples, reduces thermal conductivity by up to 35%, electrical resistivity by up to 67%, increases Seebeck coefficient by up to 23% and as a consequence increases ZT for ball milling preatreatment by 28%, for mixing preatreatment by 71% and for infiltrating by 250%. A range of films were also produced using a spin coating technique, with thicknesses ranging from 200 nm, for single sol gel layers, up to ~ 32μm for 4 (ink + 2 sol layers) structures. Several factors such as: process conditions, substrates, surfactant and base components used, were investigated in order to improve the quality of films. Process conditions were found to be a critical factor affecting the quality of films. The use of sol infiltration of each layer and a higher preheated temperature were found to reduce surface roughness by up to 23%. The films showed good electrical resistivity ranging from 260 to 500 μΩcm. The lowest value of electrical resistivity was found to be for films annealed at 700ºC.